Optical + Near-IR Speckle Imaging With The Differential Speckle Survey Instrument at Apache Point Observatory - Davidson, James; Horch, Elliott; Majewski, Steven (Bulletin of the American Astronomical Society, 2023)
The Differential Speckle Survey Instrument (DSSI) has been successfully operating at the ARC 3.5-m telescope at Apache Point Observatory in New Mexico for over a year, providing diffraction-limited imaging in the optical. We report on commissioning efforts for two new upgrades to DSSI: 1) an internal slit mask for astrometric calibration, and 2) a near-infrared channel configuration for the instrument operating at ~1.5µm. The near-infrared channel takes the place of one of the original optical channels, while the second channel of the instrument remains configured for optical observations. However, a two-position stage has been added to this optical channel, allowing for both of the original 692nm and 880nm filters. This represents the first near-infrared diffraction-limited imaging ever performed with DSSI, and the first for the ARC 3.5-m telescope, and a major step toward routine optical+NIR simultaneous speckle imaging for a range of science projects. The benefits of the internal slit mask and near-infrared channel configuration include improved astrometric precision, reduced time on-sky for calibrations, improved detection of lower luminosity companions including brown dwarfs, and a greater wavelength span for more robust source color determinations and H-R diagram positioning of system components.
Conference Name: American Astronomical Society Meeting Abstracts ADS Bibcode: 2023AAS...24220302D
Keywords: dept.phy; ⛔ No DOI found

A New Stellar Companion to GJ 835 - Clark, Catherine A.; Horch, Elliott; Davidson, James W. (Research notes of the AAS, 2023)
Num Pages: 1
Keywords: dept.phy

A New Home for an Old Hand: The Differential Speckle Survey Instrument Goes to Apache Point - Horch, Elliott P.; Davidson, Jr., James W.; Majewski, Steven R.; Sutherland, Torrie; Shea, Melissa; Henry, Todd J. (Bulletin of the American Astronomical Society, 2023)
The Differential Speckle Survey Instrument (DSSI) was built in 2008 and in its first 14 years saw substantial use in diffraction-limited imaging projects at the WIYN Telescope, Gemini-N and Gemini-S, and the Lowell Discovery Telescope. However, the completion and commissioning of the QWSSI speckle camera at Lowell Observatory has recently created the opportunity to move DSSI to the ARC 3.5-m Telescope at Apache Point Observatory (APO) in New Mexico. We report here on the commissioning of DSSI at APO and discuss some of the early science results, which represent the first diffraction-limited images in the visible range ever obtained at the ARC Telescope. Our initial observations appear to be comparable to DSSI's earlier use at WIYN in that we can obtain 0.05-arcsecond resolution at 692 nm for stars as faint as 12th magnitude in five minutes of observing or less, and we can detect companions with magnitude differences of 4 to 5 relative to their primary stars. In the near term, the instrument will be used (1) to supplement observations for the RECONS K Stars project to survey nearby K dwarfs for companions and (2) to obtain follow-up observations of binaries identified by Kepler, TESS, APOGEE, and other sources. It will also provide a testbed for simultaneous visible and infrared speckle imaging and speckle imaging through coherent fiber bundles. The potential advantages of these two innovations include better photometry in the diffraction-limited regime and higher-quality image reconstructions overall. We gratefully acknowledge support from National Science Foundation grants AST-1909560 and AST-1910130, as well as a SEED grant from the Research Corporation for Science Advancement, in the completion of this work.
Conference Name: American Astronomical Society Meeting Abstracts ADS Bibcode: 2023AAS...24130506H
Keywords: dept.phy; ⛔ No DOI found

Identifying bound stellar companions to kepler exoplanet host stars using speckle imaging - Colton, Nicole M.; Horch, Elliott P; Everett, Mark E; Howell, Steve B; Davidson, James W., Jr.; Baptista, Brian J.; Casetti-Dinescu, Dana I (Astronomical Journal, 2021)
The Kepler mission and subsequent ground-based follow-up observations have revealed a number of exoplanet host stars with nearby stellar companions. This study presents speckle observations of 57 Kepler objects of interest (KOIs) that are also double stars, each observed over a 3-8 yr period, which has allowed us to track their relative motions with high precision. Measuring the position angle and separation of the companion with respect to the primary can help determine if the pair exhibits common proper motion, indicating it is likely to be a bound binary system. We report on the motions of 34 KOIs that have close stellar companions, three of which are triple stars, for a total of 37 companions studied. Eighteen of the 34 systems are confirmed exoplanet hosts, including one triple star, while four other systems have been subsequently judged to be false positives and twelve are yet to be confirmed as planet hosts. We find that 21 are most likely to be common proper motion pairs, 4 are line-of-sight companions, and 12 are of an uncertain disposition at present. The fraction of the confirmed exoplanet host systems that are common proper motion pairs is approximately 86% in this sample. In this subsample, the planets are exclusively found with periods of less than 110 days, so that in all cases the stellar companion is found at a much larger separation from the planet host star than the planet itself. A preliminary period-radius relation for the confirmed planets in our sample suggests no obvious differences at this stage with the full sample of known exoplanets. © 2020. The American Astronomical Society. All rights reserved.
10 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85098523712
Keywords: dept.phy; peer-reviewed

Characterizing TESS-identified Quadruple- and Higher-order Eclipsing Binaries. I. Speckle Imaging with DSSI and HRCam - Majewski, Steven; Davidson, James; Wilson, Robert; Horch, Elliott; McKee, P.; Fagan, Evan; Hartwell, Gary; Kostov, Veselin; Adams, C.; Sutherland, Torrie; Tokovinin, Andreï; Wilson, John (The Astrophysical Journal, 2025)
Abstract NASA’s TESS mission has unveiled a plethora of eclipsing binaries (EBs), among them hundreds of triples and higher-order, hierarchical systems. These complex targets require follow-up observations to enable full characterization of system architectures and identify the most compact multiples expected to undergo the most dramatic dynamical evolution. We report first results from a long-term effort to perform such follow-up, focusing here on multiband speckle imaging of a majority (57) of the sample of 97 quadruple- and higher-order eclipsing binaries (Q+EBs) identified via TESS light curves by V. B. Kostov et al. Diffraction-limited imaging with the Differential Speckle Survey Instrument on the Astrophysical Research Consortium 3.5 m telescope and HRCam on the Southern Astrophysical Research 4.1 m telescope reveals nearly 60% of the 57 to resolve into two sources separated by ≥0 . ″ 03. For these partly resolved systems, we report derived characteristics (e.g., relative position angle, angular separation, and magnitude differences in multiple passbands) from the speckle imaging. We find those Q+EBs partly resolved with 4 m class telescopes to have significantly inflated Gaia parallax errors and large Gaia renormalized unit weight errors, particularly for systems with separations comparable to Gaia’s resolution limit (∼0 . ″ 6). For unresolved systems we report upper limits on angular and linear projected separations. We find two partly resolved Q+EBs with wide linear separations having eclipse timing variations that are therefore candidates of higher-than-quadruple multiplicity. Finally, we demonstrate how speckle imaging of resolved Q+EBs during an eclipse can clarify which speckle-resolved Q+EB subsystem is associated with a particular set of TESS eclipses.
Keywords: Angular resolution (graph drawing); Astrometry; Eclipse; Parallax; Speckle imaging; Speckle pattern; Telescope; dept.phy

Observations of binary stars with the differential speckle survey instrument. IX. Observations of known and suspected binaries, and a partial survey of be stars - Horch, Elliott P.; van Belle, Gerard T.; Davidson, James W., Jr.; Willmarth, Daryl; Fekel, Francis C.; Muterspaugh, Matthew; Casetti-Dinescu, Dana I.; Hahne, Frederick W.; Granucci, Nicole M.; Clark, Catherine; Winters, Jennifer G.; Rupert, Justin D.; et al. (The Astronomical Journal, 2020)
We report 370 measures of 170 components of binary and multiple-star systems, obtained from speckle imaging observations made with the Differential Speckle Survey Instrument at Lowell Observatory's Discovery Channel Telescope in 2015 through 2017. Of the systems studied, 147 are binary stars, 10 are seen as triple systems, and 1 quadruple system is measured. Seventy-six high-quality nondetections and 15 newly resolved components are presented in our observations. The uncertainty in relative astrometry appears to be similar to our previous work at Lowell, namely, linear measurement uncertainties of approximately 2 mas, and the relative photometry appears to be uncertain at the 0.1-0.15 mag level. Using these measures and those in the literature, we calculate six new visual orbits, including one for the Be star 66 Oph and two combined spectroscopic-visual orbits. The latter two orbits, which are for HD 22451 (YSC 127) and HD 185501 (YSC 135), yield individual masses of the components at the level of 2% or better, and independent distance measures that in one case agrees with the value found in the Gaia DR2 and in the other disagrees at the 2σ level. We find that HD 22451 consists of an F6V+F7V pair with orbital period of 2401.1 ± 3.2 days and masses of 1.342 ± 0.029 and 1.236 ± 0.026M⊙. For HD 185501, both stars are G5 dwarfs that orbit one another with a period of 433.94 ± 0.15 days, and the masses are 0.898 ± 0.012 and 0.876 ± 0.012M⊙ . We discuss the details of both the new discoveries and the orbit objects. © 2020. The American Astronomical Society. All rights reserved..
17 citations (Crossref) [2023-10-31] tex.ids: horchObservationsBinaryStars2020a tex.adsnote: Provided by the SAO/NASA Astrophysics Data System tex.adsurl: https://ui.adsabs.harvard.edu/abs/2020AJ....159..233H arXiv: 2004.03065 [astro-ph.SR] tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086596087 tex.eid: 233 type: Article
Keywords: Astrophysics - Earth and Planetary Astrophysics; Astrophysics - Instrumentation and Methods for Astrophysics; Astrophysics - Solar and Stellar Astrophysics; dept.phy; peer-reviewed

Observations with the Differential Speckle Survey Instrument. XI. First uear of observations from Apache Point Observatory - Davidson, James W.; Horch, Elliott P.; Majewski, Steven R.; Fagan, Evan; Shea, Melissa A.; Sutherland, Torrie; Wilson, Robert F.; Lesley, D. Xavier; Pellegrino, Richard A.; Leonard, Jonathan P.; Wilson, John C.; Chanover, Nancy J.; et al. (The Astronomical Journal, 2024)
The Differential Speckle Survey Instrument (DSSI) was relocated to the Astrophysical Research Consortium 3.5 m telescope at Apache Point Observatory (APO) in early 2022. Here we present results from the first year of observations along with an updated instrument description for DSSI at APO, including a detailed description of a new internal slit mask assembly used to measure the instrument plate scale from first principles. Astrometric precision for DSSI at APO during this time was measured to be 2.06 ± 0.11 mas, with a photometric precision of 0.14 ± 0.04 mag. Results of 40 resolved binary systems are reported, including two that were previously unknown to be binaries: HIP 7535 and HIP 9603. We also present updated orbital fits for two systems: HIP 93903 and HIP 100714. Finally, we report updated or confirmed dispositions for five Kepler Objects of Interest (KOIs) that were previously explored in Colton et al., using speckle imaging to discern common proper motions pairs from line of sight companions: KOI-270, KOI-959, KOI-1613, KOI-1962, and KOI-3214AB.
Keywords: dept.phy

The orbit and dynamical mass of polaris: Observations with the CHARA array - Evans, Nancy Remage; Schaefer, Gail H.; Gallenne, Alexandre; Torres, Guillermo; Horch, Elliott P.; Anderson, Richard I.; Monnier, John D.; Roettenbacher, Rachael M.; Baron, Fabien; Anugu, Narsireddy; Davidson, James W.; Kervella, Pierre; et al. (The Astrophysical Journal, 2024)
The 30 yr orbit of the Cepheid Polaris has been followed with observations by the Center for High Angular Resolution Astronomy (CHARA) Array from 2016 through 2021. An additional measurement has been made with speckle interferometry at the Apache Point Observatory. Detection of the companion is complicated by its comparative faintness—an extreme flux ratio. Angular diameter measurements appear to show some variation with pulsation phase. Astrometric positions of the companion were measured with a custom grid-based model-fitting procedure and confirmed with the CANDID software. These positions were combined with the extensive radial velocities (RVs) discussed by Torres to fit an orbit. Because of the imbalance of the sizes of the astrometry and RV data sets, several methods of weighting are discussed. The resulting mass of the Cepheid is 5.13 ± 0.28 M ⊙. Because of the comparatively large eccentricity of the orbit (0.63), the mass derived is sensitive to the value found for the eccentricity. The mass combined with the distance shows that the Cepheid is more luminous than predicted for this mass from evolutionary tracks. The identification of surface spots is discussed. This would give credence to the identification of a radial velocity variation with a period of approximately 120 days as a rotation period. Polaris has some unusual properties (rapid period change, a phase jump, variable amplitude, and unusual polarization). However, a pulsation scenario involving pulsation mode, orbital periastron passage, and low pulsation amplitude can explain these characteristics within the framework of pulsation seen in Cepheids.
Keywords: dept.phy; peer-reviewed

JWST/NIRCam 4–5 μm Imaging of the Giant Planet AF Lep b - Franson, Kyle; Balmer, William O.; Bowler, Brendan P.; Pueyo, Laurent; Zhou, Yifan; Rickman, Emily; Zhang, Zhoujian; Mukherjee, Sagnick; Pearce, Tim D.; Gagliuffi, Daniella C. Bardalez; Biddle, Lauren I.; Brandt, Timothy D.; et al. (The Astrophysical Journal Letters, 2024)
With a dynamical mass of 3 M Jup, the recently discovered giant planet AF Lep b is the lowest-mass imaged planet with a direct mass measurement. Its youth and spectral type near the L/T transition make it a promising target to study the impact of clouds and atmospheric chemistry at low surface gravities. In this work, we present JWST/NIRCam imaging of AF Lep b. Across two epochs, we detect AF Lep b in F444W (4.4 μm) with signal-to-noise ratios of 9.6 and 8.7, respectively. At the planet’s separation of 320 mas during the observations, the coronagraphic throughput is ≈7%, demonstrating that NIRCam’s excellent sensitivity persists down to small separations. The F444W photometry of AF Lep b affirms the presence of disequilibrium carbon chemistry and enhanced atmospheric metallicity. These observations also place deep limits on wider-separation planets in the system, ruling out 1.1 M Jup planets beyond 15.6 au (0.″58), 1.1 M Sat planets beyond 27 au (1″), and 2.8 M Nep planets beyond 67 au (2.″5). We also present new Keck/NIRC2 imaging of AF Lep b; combining this with the two epochs of F444W photometry and previous Keck photometry provides limits on the long-term 3–5 μm variability of AF Lep b on timescales of months to years. AF Lep b is the closest-separation planet imaged with JWST to date, demonstrating that planets can be recovered well inside the nominal (50% throughput) NIRCam coronagraph inner working angle.
Keywords: dept.phy